2020
DOI: 10.1074/jbc.ra120.013303
|View full text |Cite
|
Sign up to set email alerts
|

Garcinoic acid prevents β-amyloid (Aβ) deposition in the mouse brain

Abstract: Garcinoic acid (GA or δ-T3-13’COOH), is a natural vitamin E metabolite that has preliminarily been identified as a modulator of nuclear receptors involved in β-amyloid (Aβ) metabolism and progression of Alzheimer’s disease (AD). In this study, we investigated GA’s effects on Aβ oligomer formation and deposition. Specifically, we compared them with those of other vitamin E analogs and the soy isoflavone genistein, a natural agonist of peroxisome proliferator–activated receptor γ (PPARγ) that has therape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 47 publications
1
20
0
Order By: Relevance
“…25 Our in vivo data unequivocally demonstrate that both intestinal and liver PXR respond to the agonist activity of GA thus providing mechanistic support for the investigation of this natural compound in PXR-related diseases of the liver and gut. Furthermore, in a recent study we demonstrated a PXR agonist effect of GA in the mouse brain as well as in isolated astrocytes, 32 compatible with the role of this NR in Apo-mediated detoxification of Alzheimer disease related molecule A peptide.…”
supporting
confidence: 83%
See 1 more Smart Citation
“…25 Our in vivo data unequivocally demonstrate that both intestinal and liver PXR respond to the agonist activity of GA thus providing mechanistic support for the investigation of this natural compound in PXR-related diseases of the liver and gut. Furthermore, in a recent study we demonstrated a PXR agonist effect of GA in the mouse brain as well as in isolated astrocytes, 32 compatible with the role of this NR in Apo-mediated detoxification of Alzheimer disease related molecule A peptide.…”
supporting
confidence: 83%
“…In view of other important roles of GA and its vitamin E-derived analogues as allosteric inhibitor of 5-lipooxygenase, 34,49 and PPAR- and CYP450 activators, 13,46,32 our findings suggest that GA can be exploited as a valuable chemical probe and lead compound for medicinal chemistry explorations to disclose novel therapeutic agents for the prevention and treatment of lipotoxicity and chronic inflammatory diseases, such as atherosclerosis, 34 and non-alcoholic fatty liver disease and steatohepatitis. 50,51 Current studies are directed towards the preparation of GA (1) derivatives with improved potency, properties and metabolic stability whose results will be reported in due course.…”
mentioning
confidence: 91%
“…Altogether, the molecular activities of vitamin E and its derivatives in the brain in reducing oxidative stress renders it a major participant in combating neuroinflammation [194,199]. Translating the molecular activities of vitamin E into in vivo animal studies, a recent study demonstrated another vitamin E metabolite, garcinoic acid (GA), was effective in preventing β-amyloid deposition in the mouse brain [200]. Therefore, it is also worth noting that, vitamin E metabolites instead of the parent form, also exhibit neuroprotective activities.…”
Section: Nutritional Treatments/ Supplementationmentioning
confidence: 99%
“…These include green tea extracts [ 23 ], sinapic acids [ 24 ], curcumin [ 25 ], and S-nitrosoglutathione [ 26 ]. As well, Aβ-induced apoptosis can be inhibited by several vitamins, such as vitamin A [ 27 ], vitamin C [ 28 ], and vitamin E [ 29 ].…”
Section: Introductionmentioning
confidence: 99%